The Nature of Conflict - Cemal Eren Arbath; Quamrul H. Ashraf; Oded Galor (Center for Economic Studies and ifo Institute (CESifo), 2015)
This research establishes that the emergence, prevalence, recurrence, and severity of intrastate conflicts in the modern era reflect the long shadow of prehistory. Exploiting variations across national populations, it demonstrates that genetic diversity, as determined predominantly during the exodus of humans from Africa tens of thousands of years ago, has contributed significantly to the frequency, incidence, and onset of both overall and ethnic civil conflict over the last half-century, accounting for a large set of geographical and institutional correlates of conflict, as well as measures of economic development. Furthermore, the analysis establishes the significant contribution of genetic diversity to the intensity of social unrest and to the incidence of intragroup factional conflict. These findings arguably reflect the contribution of genetic diversity to the degree of fractionalization and polarization across ethnic, linguistic, and religious groups in the national population; the adverse influence of genetic diversity on interpersonal trust and cooperation; the contribution of genetic diversity to divergence in preferences for public goods and redistributive policies; and the potential impact of genetic diversity on economic inequality within a society.
Keywords: D74; N30; N40; O11; O43; Z13; 330; civil conflict; genetic diversity; fractionalization; polarization; interpersonal trust; preferences for public goods; economic inequality